Editorial - Paxton, Moragh (Critical Studies in Teaching and Learning, 2023)
With this issue CRiSTaL moves into its third year of publication and over the past two years we have been delighted to see increases inreadership around the world. CriSTaL is now read in over 70 countries worldwide. This reflects a growing interest in the more critical studies of teaching and learning on a global scale. Running through so much of the writing on higher education is a concern withlanguage and literacy, particularly student writing, which is understandable as students’ written texts continue to comprise the main form of assessment in higher education. In this issue language and literacy is more than simply a thread running through but rather ittakes centre stage in two of the articles. Therefore, it seems an appropriate spotlight for this editorial.